Model Pembelajaran Berbasis Zoom pada Pembelajaran Fisika - Agus Dinata, Frans; Eka Fitria, Tazha; Zaturrahmi, Zaturrahmi (UIN Alauddin Makassar, 2024)
This study aims to analyze Zoom-based learning, which includes: (1) the problems that lead to the use of Zoom-based learning in education, and (2) the variables influenced by the utilization of Zoom-based learning. The research method used is a literature review with a sample of 10 articles. Data were collected by gathering relevant scientific articles related to Zoom-based learning and then analyzing them. The results of this literature review show that the main issue driving the implementation of Zoom-based learning is the Covid-19 pandemic. Furthermore, the variable most affected by Zoom-based learning is students’ learning outcomes.